2007
DOI: 10.2105/ajph.2006.085837
|View full text |Cite
|
Sign up to set email alerts
|

Association of the Built Environment With Physical Activity and Obesity in Older Persons

Abstract: Findings suggest that neighborhood characteristics are associated with the frequency of walking for physical activity in older people. Whether frequency of walking reduces obesity prevalence is less clear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
322
5
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 405 publications
(350 citation statements)
references
References 49 publications
21
322
5
2
Order By: Relevance
“…The moderate correlation detected in the male participants is supported by research by Heyn et al, 16 as it was concluded that higher physical activity levels among elderly have a positive influence on BMI. The weak correlation found in females supports research by Burke et al, 17 who struggled to determine whether frequency of walking reduces obesity prevalence in elderly.…”
Section: Physical Activitysupporting
confidence: 72%
“…The moderate correlation detected in the male participants is supported by research by Heyn et al, 16 as it was concluded that higher physical activity levels among elderly have a positive influence on BMI. The weak correlation found in females supports research by Burke et al, 17 who struggled to determine whether frequency of walking reduces obesity prevalence in elderly.…”
Section: Physical Activitysupporting
confidence: 72%
“…For older adults, being confident to be physically active and having social support is positively correlated with PA, while feeling too old has an adverse effect (Bauman and Bull, 2007;Carlson et al, 2012). Next to individual characteristics, the relation of neighbourhood built environment factors and PA has been widely studied in the past, mainly showing that people living in highly walkable neighbourhoods tend to be more physically active (Berke et al, 2007;Frank et al, 2010;King et al, 2011;Marshall et al, 2014;Van Holle et al, 2014;Marquet and Miralles-Guasch, 2015). However, a study based on a national survey on Canadian adults reports that there is a positive association between neighbourhood greenness in a 500 m buffer around the home location and leisure-time PA (McMorris et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Pedestrian-oriented designs (e.g., continuous, barrier-free sidewalks, fourway stop signals, and pedestrian amenities) and access to recreational facilities have been shown to be positively associated with mobility in older adults. [17][18][19][20][21][22][23][24][25] Poor street conditions, heavy traffic, and excessive noise have been shown to be associated with the onset of mobility impairments 1 to 3 years later. 26,27 One study in the city of Chicago found that older adults with movement-related impairments had a fourfold higher odds of reporting severe difficulty walking when living in neighborhoods with streets in poor condition (e.g., cracks, broken curbs, potholes) compared to those living in neighborhoods with streets in good condition.…”
Section: Introductionmentioning
confidence: 99%